A Quantitative Study of Project-Based Learning for Digital Transformation Readiness in Entrepreneurship Education - Gita Hindrawati; Iwan Hermawan; Alya Hasna Fauziyyah; Dheanda Maurizta Chairunnisa; Linda Aprillianti; Naya Yasinta Ramadhanti; Rifka Uzma Wardati (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
The gap between the high interest in entrepreneurship among Indonesians and the low actual entrepreneurship rate suggests that entrepreneurship education in vocational higher education lacks an ideal curriculum-based practical model to bridge this divide while simultaneously accelerating the digital transformation of Micro, Small, and Medium Enterprises (MSMEs). This study aims to develop and evaluate a Project-Based Learning (PjBL) model integrated with an Outcome-Based Education (OBE) curriculum structure within the Digital Transformation and Technopreneurship course. A quasi-experimental approach was employed, involving 91 vocational college students in Semarang, Indonesia, over 6.5 weeks of active instruction organized into 29 groups and collaborate with 29 MSMEs. Data were analyzed using descriptive statistics. Structural Equation Modeling (SEM) was also conducted to examine the role of Project-Based Learning (PjBL) as a mediator between Entrepreneurial Support Clarity (ESC) and Digital Transformation Readiness Competency (DTRC). The study demonstrated a significant influence of PjBL in leveraging ESC (coefficient = 0.525; p less than 0.001) on DTRC. The PjBL implementation proved effective, with the proportion of students achieving an 'A' grade rising from 10.70 percent during the conceptual reinforcement stage to 96.40 percent during the real-project implementation stage. Achievement levels for course learning outcome indicators closely matched the established weightings, while Digital Readiness Assessment (DRA) results indicated that the partner MSMEs' digital maturity fell within Level 2 (Basic Digital). These findings confirm the relevance of the five PjBL criteria, as follows: centrality, driving questions, constructive investigation, autonomy, and realism, within the framework of Experiential Learning Theory. The study's novelty lies in the development of an implementation model that explicitly maps the integration of OBE, PjBL, and digital transformation instruments, offering both theoretical and practical contributions to entrepreneurship curriculum development in vocational higher education and the acceleration of MSME digital transformation in Indonesia.